2022
DOI: 10.3389/fncir.2021.787164
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mechanisms Underlying the Evolution of Connectivity in the Human Cortex

Abstract: One of the most salient features defining modern humans is our remarkable cognitive capacity, which is unrivaled by any other species. Although we still lack a complete understanding of how the human brain gives rise to these unique abilities, the past several decades have witnessed significant progress in uncovering some of the genetic, cellular, and molecular mechanisms shaping the development and function of the human brain. These features include an expansion of brain size and in particular cortical expans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 146 publications
0
16
0
Order By: Relevance
“…For this study, we focused on cortical subregion L2-3, recording from neurons down to 1200 μm laminar depth from the pia. Studying L2-3 of the human brain is of particular interest since these layers expanded disproportionally during human evolution 24 . Up to ten neurons were recorded simultaneously in whole-cell configuration, allowing us to functionally characterize these cells and to probe for synaptic connections between them (Figure 1A-C).…”
Section: Human Multineuron Patch-clamp Recordings With Large Data Sam...mentioning
confidence: 99%
“…For this study, we focused on cortical subregion L2-3, recording from neurons down to 1200 μm laminar depth from the pia. Studying L2-3 of the human brain is of particular interest since these layers expanded disproportionally during human evolution 24 . Up to ten neurons were recorded simultaneously in whole-cell configuration, allowing us to functionally characterize these cells and to probe for synaptic connections between them (Figure 1A-C).…”
Section: Human Multineuron Patch-clamp Recordings With Large Data Sam...mentioning
confidence: 99%
“…Given its importance for information processing, the development of the synapse provides an avenue for the understanding of the unrivaled cognitive abilities of humans. It has been observed that accompanied by the increase in the size of the human brain, the spine density is higher in human cortical neurons compared to other primates or rodents ( Defelipe, 2011 ; Schmidt and Polleux, 2021 ). The most prominent feature of synaptogenesis in humans is the protracted developmental window ( Liu et al, 2012 ).…”
Section: Evolutionary Perspectives On Molecular Mechanisms Of Synapto...mentioning
confidence: 99%
“…Thus, by manipulating neural activities, we can examine the molecular events that impact the destinies of synapses. Last but not least, synaptogenesis, though largely conserved, has been constantly reshaped during evolution ( Schmidt and Polleux, 2021 ), which endows humans with unprecedented cognitive capabilities and provides avenues to develop treatments and therapies for neurological disorders and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, density, composition, and maturation rates of synapses differ between species, potentially contributing to the evolutionary variation of neurotransmission properties, cognitive ability, and behavioral repertoire (14)(15)(16)(17)(18)(19)(20). For example, prolonged maturation or neoteny of human synapses has been suggested as a possible explanation for the emergence of human-specific cognitive traits (21)(22)(23). But we still know little about the underlying molecular mechanisms.…”
Section: Main Textmentioning
confidence: 99%